Post-fire forest management in southern Europe: a COST action for gathering and disseminating scientific knowledge - Barbati A; Arianoutsou M; Corona P; De Las Heras J; Fernandes P; Moreira F; Papageorgiou K; Vallejo R; Xanthopoulos G (iForest - Biogeosciences and Forestry, 2010)
Every year about 45 000 forest fires occur in Europe, burning half a million hectares of forests and rural lands; between 1995 and 2004, more than 4 million hectares burned in the Mediterranean Region alone. Post-fire management of burned areas has been given much lesser attention than combating or preventing fires. However, important questions raise public concern and call for sound scientific knowledge to undertake appropriate post-fire actions: e.g., how to evaluate fire damages in economical terms? How to manage burned areas? Is it possible to establish, in the long-term, less flammable and more fire resilient forests and landscapes? To address these questions, a network of researchers and practitioners working in the field of fire ecology and forest management from all around Europe has been established in the frame of “COST Action FP0701-Post-Fire Forest Management in Southern Europe”, supported by the European Union Research and Technology Development Framework Program. The Action aims to: i) develop and disseminate scientifically based decision criteria for planning post-fire forest management, from the stand to the landscape level; ii) translate this scientific knowledge into management practices; iii) connect scientists and stakeholders for exchanging experiences, evaluating these practices, and putting them into practice. To achieve these objectives the scientific groups involved will a) review and summarize the current scientific knowledge on post-fire management in Europe, by gathering and evaluating the results of previous and ongoing research; b) translate this knowledge into technical recommendations, by producing thematic reports, a book on the state-of-the-art of scientific knowledge on post fire assessment, and an electronic handbook on post-fire restoration; c) disseminate this knowledge to stakeholders, practitioners and decision makers. Besides publications and a project website already active (http://uaeco.biol.uoa.gr/cost/), training schools and one major conference will be organized. Although focused on Southern Europe, the outcomes of this Action will be crucial for central and northern European countries as well, as climate change and land use changes often leading to more homogeneous and expanding forest areas are already increasing fire hazard in those regions.